‘Beware of false prophets’: A Fragment of the Old Swedish Miracle Homily Book. - Adams, Jonathan (Medieval Sermon Studies, 2016)
The article comprises an introduction to and an edition and translation of an Old Swedish sermon fragment found in the Hannaas Collection at the Ethno-Folkloristic Archive, University of Bergen, Norway (Hannaas 66). This previously unpublished paper fragment is one of the missing parts of the Old Swedish Homily Book (known as Svensk järteckens postilla), dating from the second half of the fifteenth century and now housed at the Royal Library in Stockholm, Sweden (Cod. Holm. A 111). The text in Hannaas 66 comprises a sermon for the 8th Sunday after Trinity based on Matthew 7. 15–16 and includes a miracle exemplum that illustrates the importance of acting justly and following the will of God.